ÔNIBUS ELÉTRICO – CAMINHOS PARA UM TRANSPORTE SUSTENTÁVEL E MAIS EFICIENTE. - Silva, Evelyn Tânia Carniatto (2022)
The need for new energy sources and new technologies has been increasing worldwide due to the environmental issue and the concern with global energy crises. The Paris Climate Agreement, or the United Nations Climate Change Conference Paris 2015 (COP21), decisions compelled countries to explore more sustainable, clean and zero carbon technologies and products, being confirmed in 2021, at Climate Change Conference (COP26), which took place in Ireland. This research tries to answer whether the global main trend in the transport model from combustion to electric traction is a promising approach to achieve the Sustainable Development Goals - SDGs in the Brazilian scenario, which can contribute to the climate change solution. In this case study, a quantitative field research was carried out, in which, supported by relevant bibliographies, some indicators were explored as: urban bus lines in Cascavel city, Paraná, Brazil, their average mileage, emission and energy efficiency when compared to electric buses. The Life Cycle precept, also called Well to Wheels, was used to analyze emissions according to the driving force of buses and their energy sources. The results showed a 95.98% reduction in emissions in gCO2eq/km using electricity from the national grid, taking as reference the Brazilian electricity matrix as predominantly renewable and a 98.37% reduction in emissions in gCO2eq/km, using as a source a photovoltaic system. This confirms the sustainable potential of these systems to contribute to the solutions of the planetary climate emergency. This study was financed in part by the Coordenação de Aperfeiçoamento de Pessoal de Nível Superior - Brasil (CAPES) - Finance Code 001.